Association between advanced lung cancer inflammation index and atherosclerosis cardiovascular disease in U.S. adults: a population-based investigation - Xiang, Zhongtian; Lin, Sheng; Yang, Bei; Zhu, Siman; Song, Qian (Frontiers in Nutrition, 2025)
The advanced lung cancer inflammation index (ALI) is a multifaceted tool that combines indicators of inflammation and nutritional status to evaluate patient’s health conditions. Globally, atherosclerotic cardiovascular disease (ASCVD) remains a leading cause of both morbidity and mortality. Considering the pivotal role of inflammation in cardiovascular disease, investigating the relationship between ALI and ASCVD makes sense. A vast amount of information was gathered from the 1999 to 2018 National Health and Nutrition Examination Survey (NHANES). Univariate and multivariate logistic regression models were employed, supplemented by subgroup analyses and interaction tests. Furthermore, smooth curve fitting was applied to examine linear relationships, while the binary linear regression model was utilized to ascertain the threshold effects. The predictive capabilities of the Systemic Immune-Inflammation Index, Platelet-to-lymphocyte Ratio and ALI for ASCVD were evaluated using Receiver Operating Characteristic (ROC) curves with the area under the curve (AUC) values. A cross-sectional study of 48,845 individuals was included in the study. The ALI demonstrated an inverse association with the likelihood of ASCVD in participants [Odds ratios: 0.87, 95% confidence interval (CI): 0.82 to 0.92]. Sex had a significant interaction impact, according to subgroup analyses (P for interaction < 0.05). Furthermore, ALI emerged as a more accurate predictor of ASCVD, with the AUC values of 0.608, surpassing both the systemic immune-inflammation index (AUC = 0.502) and the platelet–lymphocyte ratio (PLR) (AUC = 0.569). This study provides evidence that higher ALI levels are associated with a lower probability of ASCVD prevalence in adult Americans. These findings suggest that ALI may serve as a valuable anthropometric marker for predicting ASCVD prevalence.